Scalar politics, language ideologies, and the sociolinguistics of globalization among transnational Korean professionals in Hong Kong. (11th July 2016) - Bailey, Adrian J.; Canagarajah, Suresh; Lan, Shanshan; Powers, Devereux Gong
Abstract : This paper argues that the sociolinguistics of globalization is accompanied by a constitutive scalar politics. Based on ten interviews with Korean professionals in Hong Kong, we report that Korean migrants' use and experience of English is characterized by competing language ideologies we identify as: Pragmatic English/Perfect English, Multilingualism/English Only, and Global Language/Local Language. Tensions within these ideologies were revealed as respondents referenced the contexts of their daily lives as intersecting sets of geographic, temporal, and social scales. We discuss how sociolinguistic relations associated with the transnational lifecourse, hybridizing identity, and racialization were imagined in ways that re‐negotiated these scales to serve the interests of the participants and provide coherence to their communicative practices. Sociolinguistic relations both reference scales and constitute them. We conclude that attending to scales and scalar politics provides a better explanatory framework for the ways the uneven linguistics markets of globalization are negotiated by transnational subjects. Abstract : 本文认为全球化的社会语言学与尺度政治是相互辅助的关系。基于对十位香港韩裔专业人士的访谈资料, 我们发现韩裔移民对英语的运用和体验反映出几种相互竞争的语言意识形态:实用英语/完美英语, 语言多元化/单一英语, 全球语言/地方语言。这些语言意识形态之间的张力体现为地域、时间和社会尺度在受访者日常生活中的互相交错。我们探讨与跨国人生历程, 身份混杂化, 和种族化相关的社会语言关系如何重新协调这些尺度, 使受访者受益并为他们的沟通实践提供连贯性。社会语言关系不仅指代尺度而且建构尺度。在结论里我们认为关注尺度及尺度政治为跨国主体协调不均衡的全球化语言学市场提供了一个更好的诠释框架。